Effects of nebulized dexmedetomidine for premedication on the parameters of oxidative and inflammatory stress in children undergoing tonsillotomy and adenoidectomy: A pilot randomized controlled trial - Vesna V. Stevanovic; Ana D. Mandras; Ana A. Djuric; Ivan A. Soldatovic; Dragana V. Bojanin; Branko Lj. Lukic; Predrag D. Stevanovic; Marija M. Stevic; Aleksandar M. Vlahovic (PLoS ONE, 2026)
Background This prospective randomized clinical pilot study aimed to evaluate the effect of inhaled Dexmedetomidine in premedication in children after tonsillectomy with adenoidectomy on oxidative and inflammatory stress and the drugs impact on clinical parameters such as perioperative sedation, hemodynamics, respiratory function, postoperative delirium, analgesia, opioid consumption and frequency of complications. Methods Children aged 4–13 years with an indication for tonsillotomy with adenoidectomy were randomized into two groups: (D) – Dexmedetomidine treated group and (N) – control, non-treated group. Ramsey’s sedation score, Bispectral index (BIS), and vital signs (heart rate, respiratory rate, noninvasive blood pressure and hemoglobin oxygen saturation) were monitored perioperatively in at defined time points. After 15 minutes of extubation, the postoperative delirium score (PEAD) and pain score (VAS) were noticed. Pain scores were monitored for up to 12 postoperative hours every three hours on the ward. Venous blood samples were taken before intervention and after surgery to evaluate redox homeostasis (levels of malondialdehyde – MDA, nitrogen monoxide, glutathione and sulfhydryl groups and the activity of superoxide dismutase and catalase) and inflammatory parameters (blood count, neutrophile/lymphocyte ratio, C-reactive protein and Interleukin 6). Perioperative complications in the induction phase, intraoperative and postoperative period, as well as the consumption of opioids, were noted. Results 16 patients in the D and 15 in the N groups participated in the study. There was no difference in age, sex, body weight and duration of surgery between the two groups. The obtained results of oxidative stress and inflammatory response markers showed that there was a statistically significant difference in the MDA level between compared groups (postoperative MDA 88.93 ± 1.19 vs. 95.05 ± 1.58, ΔMDA 0.014), with no difference observed in other investigated oxidative and inflammatory stress in plasma samples. Patients in both groups were hemodynamically and respiratory stable. Still, patients in the treated (D) group achieved the desired level of sedation compared to the control evaluated by the Ramsey sedation score (p < 0.001). The BIS values were statistically significantly different between the D and N groups 30 minutes after inhalation (86.6 ± 11.6 vs. 98.1 ± 1.2, P < 0.001), but showed no differences during and after the procedure. The two groups had a significant difference in pain control upon awakening and one hour after the operation, respectively (pain on awakening p = 0.024; pain during the first hour of stay in the ward p = 0.039). The consumption of intraoperative opioids was slightly lower in the D group than in the N group (D vs. N group: fentanyl in µg/kg mean 3.67 ± 0.78 vs. 3.94 ± 1.12, p = 0.445, i.e., alfentanil in µg/kg mean 2.02 ± 1.85 vs. 2.30 ± 2.08, p = 0.691). Also, there were no differences in observed perioperative complications between groups. Conclusion Inhaled Dexmedetomidine at a dose of 2 µg/kg in premedication reduces oxidative stress. However, the statistical significance of this drugs effect on the level of markers of antioxidant defense and inflammation has not been proven in children operated on for tonsillar hypertrophy. This dose regimen and route of application of Dexmedetomidine significantly affect the degree of perioperative sedation and BIS values, provides perioperative hemodynamic and respiratory stability, significant immediate postoperative analgesia, and reduces the consumption of analgesics with minimal complications, which makes it useful for shorter surgical interventions.